Equivalence Problems in an Indonesian Target Text Translated by Machine Translation on J.K Rowling’s Harry Potter and the Order of the Phoenix - Amaliah (GoAcademica Research & Publishing, 2023)
This research is aimed at finding the equivalence problems in Machine Translation at word level, above word level, grammatical level, textual level, and pragmatic level. Method used is qualitative research to analyze the problems of equivalence found in the translation of Harry Potter: The Order of Phoenix. The data are taken randomly from the ten chapters of the Harry Potter book, and the findings were categorized into the five problems of translation equivalence. The data displayed two languages: a Source Text is in English, and the Target Text is in Bahasa Indonesia. This research used the theory of Mona Baker (2018) regarding equivalence levels through post editing on analyzing MT output. The translation of Harry Potter's work is still imprecise on a lexical level. Many idioms serve as figures of speech at the word level or higher. Many words and sentences were incomprehensible at the textual level; therefore, post-editing was performed to preserve the flow and logic of the original language. There are grammatical distinctions between English and Indonesian. The last is a pragmatic one, focusing on the practical use of words in everyday conversations. Teaching and learning a language through translation requires reading ability and knowledge.